Effects of changing clinical practice on costs and outcomes of percutaneous coronary intervention between 1998 and 2002. Issue 2 (18th July 2006) - Denvir, M A; Lee, A J; Rysdale, J; Prescott, R J; Eteiba, H; Starkey, I R; Pell, J P; Walker, A
Abstract : Aim: To assess the effect of changing clinical practice on the costs and outcomes of percutaneous coronary intervention (PCI) between 1998 and 2002. Setting: Two tertiary interventional centres. Patients: Consecutive patients undergoing PCI over a 12-month period between 1998 and 2002. Design: Comparative observational study of costs and 12-month clinical outcomes of consecutive PCI procedures in 1998 (n = 1047) and 2002 (n = 1346). Clinical data were recorded in the Scottish PCI register. Repeat PCI, coronary artery bypass graft and mortality were obtained by record linkage. Costs of equipment were calculated using a computerised bar-code system and standard National Health Service reference costs. Results: Between 1998 and 2002, the use of bare metal stents increased from 44% to 81%, and the use of glycoprotein IIB/IIIA inhibitors increased from 0% to 14% of cases. During this time, a significant reduction was observed in repeat target-vessel PCI (from 8.4% to 5.1%, p = 0.001), any repeat PCI (from 11.7% to 9.2%, p = 0.05) and any repeat revascularisation (from 15.1% to 11.3%, p = 0.009) within 12 months. Significantly higher cost per case in 2002 compared with 1998 (mean (standard deviation) £2311 (1158) v £1785 (907), p<0.001) was mainly due to increased contribution from bed-day costs in 2002 (45.0% (16.3%) v 26.2% (12.6%), p = 0.01) associated with non-elective cases spending significantly longer in hospital (6.22 (4.3) v 4.6 (4.3) days, p = 0.01). Conclusions: Greater use of stents and glycoprotein IIb/IIIa inhibitors between 1998 and 2002 has been accompanied by a marked reduction in the need for repeat revascularisation. Longer duration of hospital stay for non-elective cases is mainly responsible for increasing costs. Strategies to reduce the length of stay could considerably reduce the costs of PCI.